Free Vascularized Fibula Flap Reconstruction of Total and Near-total Destabilizing Resections of the Sacrum. Issue 6 (June 2021) - Asaad, Malke; Mericli, Alexander F.; Hanasono, Matthew M.; Roubaud, Margaret S.; Bird, Justin E.; Rhines, Laurence D.
Abstract : Background: Vascularized bone grafts (VBGs) are associated with improved union and fewer instrumentation complications in the mobile spine. It is not known if VBGs are similarly efficacious after sacrectomy. Methods: We conducted a retrospective chart review of all patients who underwent total sacrectomy and immediate reconstruction with VBG between 2005 and 2019. Patient and surgical characteristics in addition to union and functional outcomes were analyzed. Results: We identified 10 patients (6 women and 4 men) with a mean age of 42 years (range, 12–71 years). All patients received iliolumbar instrumentation as well as a free fibula flap as a VBG. There were no complications at the fibula flap donor site or specifically related to the VBG. Bony union was achieved in 7 (88%) of 8 patients with an average union time of 6.3 months (range, 2–10 months). Surgical complications occurred in 5 patients, 4 patients required reoperation for wound dehiscence, and 1 patient required conversion to a 4-rod construct and bone grafting for instrumentation loosening and partial nonunion. Instrumentation failure developed in 1 patient, but no surgical intervention was required. One patient was able to walk independently without any limitation, 5 patients required a walker, 2 were wheelchair-bound except for short (<15 ft) distances, and 2 were lost to follow-up. Conclusions: The free vascularized fibula flap is a safe and effective option for supplementing spinal reconstruction after destabilizing sacrectomy.